A Content Analysis of Safety Behaviors of Television Characters: Implications for Children's Safety and Injury - Richard Potts etal (Journal of Pediatric Psychology, Vol. 21, No. 4, 1996, pp. 517-528, 1996)
Examined frequency and characteristics of safety behaviors in television programs popular with child audiences. A sample of52 programs was coded for safety event location, demographic characteristics of safety models, social and physical contexts of safety events, and successful or unsuccessful outcomes of safety behaviors. Results indicate an overall rate of 13 safety behaviors per hour, with over half of all safety behaviors located in commercial advertisements. Most safety behaviors were performed by male adult characters, had limited relevance for children, and were not associated with either positive or negative outcomes. Findings are discussed in terms of their relevance for observational learning of safety behaviors by child viewers.